Optical sudy of PKS B1322-110, the Intra-hour Variable Radio Source - Madrid, Juan P. (2020)
Observations with the Australia Telescope Compact Array revealed intrahour variations in the radio source PKS B1322-110. As part of an optical follow-up, we obtained Gemini Hα and Hα continuum (HαC) images of the PKS B1322-110 field. A robust 19σ detection of PKS B1322-110 in the Hα-HαC image prompted us to obtain the first optical spectrum of PKS B1322-110. With the Gemini spectrum we determine that PKS B1322-110 is a flat-spectrum radio quasar at a redshift of z = 3.007 ± 0.002. The apparent flux detected in the Hα filter is likely to originate from He II emission redshifted precisely on the Galactic Hα narrowband filter. We set upper limits on the emission measure of the Galactic plasma, for various possible cloud geometries.